ANTIMICROBIAL ACTIVITY OF LOCALLY PRODUCED BLACK SOAPS SOLD IN AGBOR, DELTA STATE, NIGERIA - Chijindu, Pass; Jaboro, Grandy; Oshilonyah, Lucy; Oyibe, Augustina (FUDMA JOURNAL OF SCIENCES, 2026)
Antimicrobial resistance is a key global health challenge, particularly in developing regions where access to medicated hygiene products is limited. Locally produced black soap in Agbor, Delta State, Nigeria, holds cultural significance and is widely used for skin care. However, scientific evaluation of its antimicrobial efficacy and quality remains insufficient. Black soap samples were collected from three major markets in Agbor and tested for antimicrobial activity against Staphylococcus aureus, Candida albicans, and Escherichia coli using agar well diffusion, minimum inhibitory concentration, and minimum bactericidal concentration assays. Physicochemical properties including pH, total alkali, free fatty matter, and moisture content were also analyzed. Data were statistically evaluated to assess correlations between properties and antimicrobial effectiveness. All black soap samples showed antimicrobial activity, with greater inhibition observed against S. aureus and C. albicans compared to E. coli. The soaps exhibited alkaline pH and varied physicochemical parameters depending on source and formulation. Soaps with higher free fatty matter and moderate alkali content generally showed stronger antimicrobial effects, whereas excessive alkali could pose skin irritation risks. The study provides evidences, supporting the antimicrobial efficacy of locally produced black soap in Agbor. Variation in quality highlights the need for standardization to ensure consistent antimicrobial performance and consumer safety. These findings support the integration of indigenous hygiene products in public health strategies.
Keywords: Antimicrobial efficacy; Black soap; Staphylococcus aureus; Escherichia coli; Candida albicans; Traditional hygiene practices; Public health